1993
DOI: 10.1111/j.1365-2621.1993.tb06175.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Profiles of Fermenting Wheat Sour Doughs

Abstract: The free amino acid patterns of unfermented and fermented wheat sour doughs started with Lactobacillus plantarum were related by factor analysis to dough yield, ash content of flour, fermentation temperature and presence/absence of yeast, from data corresponding to a central composite design of samples. Individual levels of hydrophobic, acid and basic amino acids as well as total amino acid content positively correlated with extraction rate of flours. The presence of yeast promoted metabolism of histidine, asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 13 publications
3
6
0
Order By: Relevance
“…This study confirmed the importance of ash content of flour on the formation of amino acids during sourdough fermentation as reported in earlier studies (Spicher and Nierle 1988;Collar et al 1993;Collar and Martinez 1995). The important role of flours with a higher extraction rate is based on the presence of endogenous endo-and exoproteolytic activity in bran-rich flour (Loponen et al 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This study confirmed the importance of ash content of flour on the formation of amino acids during sourdough fermentation as reported in earlier studies (Spicher and Nierle 1988;Collar et al 1993;Collar and Martinez 1995). The important role of flours with a higher extraction rate is based on the presence of endogenous endo-and exoproteolytic activity in bran-rich flour (Loponen et al 2004).…”
Section: Discussionsupporting
confidence: 90%
“…The degree of proteolysis and the amount of acids and volatile compounds formed depend both on what kind of lactic acid bacteria and yeasts are present and on the process parameters of sourdough fermentation such as fermentation time and temperature, dough yield, ash content of flour, and the presence of oxygen. Individual effects of ash content of flour, fermentation temperature and time, and dough yield on the formation of acidity, volatile compounds, and amino acids have been partly elucidated in earlier studies, but the interactions of these factors have not been studied systematically Collar 1993;Hansen and Hansen 1994a;Collar and Martinez 1995;Gobbetti et al 1995).…”
mentioning
confidence: 99%
“…Similar increases of FAA content were also reported during fermentation of Parkia biglobosa, Prosopis africana, and soybean seeds [2,28,29]. This increase suggests some proteases activity emanating from the metabolism of the microorganisms involved in the fermentation [30,31]. During alkaline fermentation, proteolytic activity is reported to increase, as well as the main metabolic activity of the microorganisms [2,28,32].…”
Section: Resultssupporting
confidence: 70%
“…Proteolytic activity has been characterized only by determination of the amino acid concentration after sourdough fermentation and it has been shown to depend on the species of bacteria, on processing conditions (temperature and dough yield), and on the co-presence of yeasts which utilize amino acids, reducing their final concentration. Statistical analysis has been applied to study the amino acid profile in both fermented (with Lactobacillus plantarum) and unfermented wheat sourdoughs (16). The noticeable decrease in the concentration of free amino acids in the crust of bread has been explained by nonenzymatic browning which occurs during baking (5).…”
Section: Introductionmentioning
confidence: 99%